World leaders' usage of Twitter in response to the COVID-19 pandemic: a content analysis - Rufai, Sohaib R; Bunce, Catey (Journal of public health (Oxford, England), 2020)
It is crucial that world leaders mount effective public health measures in response to COVID-19. Twitter may represent a powerful tool to help achieve this. Here, we explore the role of Twitter as used by Group of Seven (G7) world leaders in response to COVID-19. This was a qualitative study with content analysis. Inclusion criteria were as follows: viral tweets from G7 world leaders, attracting a minimum of 500 'likes'; keywords 'COVID-19' or 'coronavirus'; search dates 17 November 2019 to 17 March 2020. We performed content analysis to categorize tweets into appropriate themes and analyzed associated Twitter data. Eight out of nine (88.9%) G7 world leaders had verified and active Twitter accounts, with a total following of 85.7 million users. Out of a total 203 viral tweets, 166 (82.8%) were classified as 'Informative', of which 48 (28.6%) had weblinks to government-based sources, while 19 (9.4%) were 'Morale-boosting' and 14 (6.9%) were 'Political'. Numbers of followers and viral tweets were not strictly related. Twitter may represent a powerful tool for world leaders to rapidly communicate public health information with citizens. We would urge general caution when using Twitter for health information, with a preference for tweets containing official government-based information sources.